The Effect of Wall Materials and Drying Methods on The Encapsulation Sardinella lemuru Smart Flavor - Azkiyah, Lailatul; Witono, Yuli; Taruna, Iwan; Choiron, Miftahul; Wahyuni, Livia; Nafi', Ahmad; Belgis, Maria; Masahid , Ardiyan Dwi; Aini, Anggita Arifatul (Department of Technology of Agricultural product (THP) Jambi University, 2024)
Antioxidant compounds in food are generally less stable when applied to food, so technology is needed to help antioxidant compounds become more stable during storage, one of which is microencapsulation. The research aims to determine the effect of the wall material ratio and drying methods on the characteristics of Sardinella lemuru smart flavor microcapsules. The experimental design used was a two-factor Complete Random Design (CRD): ratio of wall materials (maltodextrin: Arabic gum) and drying methods (spray drying and freeze drying). The research showed that enzyme activity ranged from 14.81-52.64 U/mL; lightness 95.2-100; yield 4.00-17.19%; water content 2.26-9.15%; antioxidant activity 15.75-31.23%; encapsulation efficiency 69.06-78.47%. Microcapsules with the highest water content, lightness, antioxidant activity, and encapsulation efficiency were at the ratio wall materials (maltodextrin: Arabic gum) of 7:3 by spray drying, 9.15%, 100, 31.23%, and 78.47%. On the other hand, the highest yield (17.19%) was at the ratio wall materials (maltodextrin: Arabic gum) 8:2 by freeze-drying. The morphology of the microcapsules by spray drying is spherical, and freeze drying makes it flaky and sharp.